2008
DOI: 10.1074/jbc.m800754200
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 Activation Plays a Regulatory Role in Pancreatic Amylase Secretion

Abstract: Rap1 is a member of the Ras superfamily of small GTP-binding proteins and is localized on pancreatic zymogen granules. The current study was designed to determine whether GTPRap1 is involved in the regulation of amylase secretion. Rap1A/B and the two Rap1 guanine nucleotide exchange factors, Epac1 and CalDAG-GEF III, were identified in mouse pancreatic acini. A fraction of both Rap1 and Epac1 colocalized with amylase in zymogen granules, but only Rap1 was integral to the zymogen granule membranes. Stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 58 publications
4
63
0
1
Order By: Relevance
“…PACAP or CCK alone has little effect on amylase secretion from pancreatic acinar cells, while in combination they markedly increase the amylase secretion by sensitizing the acinar cells to CCK-induced zymogen activation (12). Epac/Rap1 signals play an essential role as a common signal for both CCK-and cAMP-evoked amylase secretions in pancreatic acinar cells (24). In our previous study, we demonstrated that cAMP /Epac /Rap1 may be involved in PACAP-induced gene expression and neurite extension in PC12 cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…PACAP or CCK alone has little effect on amylase secretion from pancreatic acinar cells, while in combination they markedly increase the amylase secretion by sensitizing the acinar cells to CCK-induced zymogen activation (12). Epac/Rap1 signals play an essential role as a common signal for both CCK-and cAMP-evoked amylase secretions in pancreatic acinar cells (24). In our previous study, we demonstrated that cAMP /Epac /Rap1 may be involved in PACAP-induced gene expression and neurite extension in PC12 cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Rap activation is important for lymphocyte migration in vivo (53,54). The Rap-dependent signaling pathway activated by Epac is known to be cell-specific (55,56), and there is evidence for Rap-mediated action of Epac to stimulate mitogen-activated protein kinases (p38, extracellular signal-regulated kinase 1/2) in neurons, endocrine cells, and T-cells (57)(58)(59). Rap1 was reported to be activated by PKA through the phosphorylation of Rap1GAP (60), consistent with our finding that treatment of LAK cells with IL-8 or PKA activator did not show Rap1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxidase activity was visualized using the SuperSignal West Femto sensitivity substrate kit (Pierce). Rap1 activation was determined as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
“…After overnight incubation, isolated mouse pancreatic acini were allowed to settle in test tubes and then fixed for 1 h at room temperature with 4% paraformaldehyde in PBS. Acinar preparations were rinsed with PBS, cryoprotected, and frozen as previously described (35). Cryostat sections were incubated with Alexa 594-conjugated phalloidin (1:50 dilution), which stains filamentous actin (F-actin).…”
Section: Methodsmentioning
confidence: 99%